Tarannum Smart Learning Application: Embracing the Beauty of Tarranum Through Multimedia Technology - Hapini Awang; Abdulrazak F. Shahatha Al-Mashhadani; Ramlan Mustapha; Mohd Faiz Mohd Yaakob; Adnan Mohamed Yusof; Nusairah Ramli; Mohd Nur Adzam Rasdi; Mohd Fairuz Jafar; Aliff Nawi; Farah Muhamad Zain; Marini Kasim; Mohd Zaini Bin Zakaria (Institute of Advanced Engineering and Science (IAES) in collaboration with Intelektual Pustaka Media Utama (IPMU), 2024)
Indexed by SCOPUS